Manajemen Kepemimpinan Yakub (Israel) - Janovi, Evindra; Samuel, Reinhard; Aprilina, Aprilina; Sarmauli, Sarmauli (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Leadership is an essential element in shaping the direction and success of a community, whether in social, spiritual, or organizational contexts. The figure of Jacob, also known as Israel, in the biblical narrative, presents a model of leadership that is both complex and rich in values. Through his challenging life journey from conflict with Esau, experiences in Laban’s household, to his role as the head of a large family Jacob demonstrates management principles that remain relevant in modern settings. He was able to resolve conflicts through diplomatic approaches, delegate responsibilities systematically, and foster harmonious family relationships. From the perspective of Theological Management, Jacob’s leadership places God at the center of every decision, reflecting integrity, patience, and empathetic communication.